Advances in the design of new epoxy supports for enzyme immobilization–stabilization. (23rd November 2007) - Mateo, C.; Grazú, V.; Pessela, B.C.C.; Montes, T.; Palomo, J.M.; Torres, R.; López-Gallego, F.; Fernández-Lafuente, R.; Guisán, J.M.
Abstract : Multipoint covalent immobilization of enzymes (through very short spacer arms) on support surfaces promotes a very interesting 'rigidification' of protein molecules. In this case, the relative positions of each residue of the enzyme involved in the immobilization process have to be preserved unchanged during any conformational change induced on the immobilized enzyme by any distorting agent (heat, organic solvents etc.). In this way, multipoint covalent immobilization should induce a very strong stabilization of immobilized enzymes. Epoxy-activated supports are able to chemically react with all nucleophile groups placed on the protein surface: lysine, histidine, cysteine, tyrosine etc. Besides, epoxy groups are very stable. This allows the performance of very long enzyme–support reactions, enabling us to get very intense multipoint covalent attachment. In this way, these epoxy supports seem to be very suitable to stabilize industrial enzymes by multipoint covalent attachment. However, epoxy groups exhibit a low intermolecular reactivity towards nucleophiles and hence the enzymes are not able to directly react with the epoxy supports. Thus a rapid physical adsorption of enzymes on the supports becomes a first step, followed by an additional rapid 'intramolecular' reaction between the already adsorbed enzyme and the activated support. In this situation, a suitable first orientation of the enzyme on the support (e.g. through regions that are very rich in nucleophiles) is obviously necessary to get a very intense additional multipoint covalent immobilization. The preparation of different 'generations' of epoxy supports and the design of different protocols to fully control the first interaction between enzymes and epoxy supports will be reviewed in this paper. Finally, the possibilities of a directed immobilization of mutated enzymes (change of an amino acid by cysteine on specific points of the protein surface) on tailor-made disulfide-epoxy supports will be discussed as an almost-ideal procedure to achieve very intense and very efficient rigidification of a desired region of industrial enzymes.